Pengaruh Bibliotherapy dan Snake Ladder Game’s Therapy terhadap Tingkat Kooperatif Anak selama Hospitalisasi - Rahmah Widyaningrum; Ignasia Nila Siwi (JURNAL INFO KESEHATAN, 2019)
Children who were hospitalized in 2017 were 3.21% with the percentage of school-age children 47.62%. Hospital is a planned or emergency process where children are required to undergo treatment at the hospital. The reaction of child hospitalization varies, depending on the stage of development, previous illness experiences, support systems, and the children's coping abilities. One of the stressors of pediatric hospitalization is the complexity of the therapeutic procedures provided by nurses and medical teams. The study aims to play therapy as one method in reducing anxiety and increasing children's cooperation during undergoing treatment procedures. The research method was Pre-Experimental Research with One Group Pretest-Posttest approach. A sample of 20 children was with a simple random sampling technique. The study was conducted in April-September 2019 in the Children's Ward of Yogyakarta City Public Hospital. Inclusion criteria: children were first admitted to the hospital on the first or second day; children aged 7-12 years; had no physical disabilities, cognitive and language disorders; had sufficient physical ability to take part in the game. The results of data analysis using paired t-test obtained p value<0.001 with a pretest value of 16.55 ± 6.88 and post-test 26.45 ± 1.79. The conclusion of the research shows that there is an effect of giving Bibliotherapy and Snake-Ladder Game Therapy in increasing the cooperative level of children in undergoing nursing actions during hospitalization. Researchers recommend this play therapy as one of the permanent procedures for independent nursing actions in each child's ward.